COASTLINE CHANGES IN INDRAMAYU REGENCY BETWEEN 1989-2019 - Kusnanto; Setiawan, Yudi; Nurjaya, I Wayan (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2022)
Basically, coastline changes include accretion (raised soil) and abrasion. This study aims to analyze coastline changes in the Indramayu Regency between 1989 and 2019, as well as the causing factors. The secondary data were obtained from Landsat 5 Satellite Imagery in 1989, 1999, 2009, and Landsat 8 in 2019. This analysis used BILKO method, which is a Landsat image analysis to separate land and sea areas. Then overlay method, which was used to delineate boundary. Spatial analysis showed coastline changes in the Indramayu regency of both accretion and abrasion. In the 1989-1999 period, there was an accretion of 319 ha, while there was an abrasion 1291 ha. Furthermore, in the 1999-2009 period, there was an accretion of 349 ha, and abrasion of 1125 ha. Also, in the 2009-2019 period, there was an accretion of 698 ha, and abrasion of 358 ha. Meanwhile, the factors that cause coastline changes are natural such as wind, waves, currents, as well as human factors such as the conversion of mangrove land to ponds and also planting activities. Therefore, efforts made by the government are making waves containment tool and planting mangrove vegetation.